The Analysis of English Pronunciation Errors by English Education Students of FKIP UMSU - Yusriati Yusriati; Selamat Husni Hasibuan (Journal of English Education and Teaching, 2019)
Pronunciation is one important thing that must be mastered by the students who studies English. Good Pronunciation makes students’ English speaking skills becomes better. This research aimed at analyzing the errors made by students of English education department of FKIP UMSU in pronouncing English words. The objectives of this study were 1) to describe the opinions of English education students about their English pronunciation skills so far; 2). to analyze the forms of English pronunciation errors made by the students; 3) to explore strategies or efforts made by students to improve their English pronunciation skills; 4) to Identify obstacles found by the students in English pronunciation. Descriptive qualitative design was used  in this research. The data were obtained by doing the interview and asking the students to pronounce some English words in specific topic. The findings of this research revealed that students had various opinion about their ability in English pronunciation. Some students thought that they had good English pronunciation skills; some students thought that their ability in pronouncing English words was better than before and some other students still thought that their English pronunciation skills were not good. Based on the analysis of data, the students still made some errors in pronouncing English words. In order to improve their pronunciation, the students used some strategies such as watching YouTube in English and using google voice application.